Artificial Intelligence and Applications in PM&R. (November 2019) - Anderson, Dustin
Abstract : Abstract: Artificial intelligence methods are being applied broadly in society and increasingly in health care and research. Machine learning, a subset of artificial intelligence, represents the study of algorithms that improve automatically with experience. This article provides a basic overview of artificial intelligence, machine learning categories, common applications in the business sphere, advantages and disadvantages of using this technology, and example applications in rehabilitation and other fields for contextual purposes. The study and implementation of machine learning and artificial intelligence can function to improve patient care and represents a burgeoning area of research.